Geoelectrical survey in three areas in Barton Peninsula near the King Sejong Korean Antarctic Station - Correia, Antonio (2017)
With the objective of trying to find a correlation between electrical resistivity values of the ground and the existence of different kinds of mosses and liquens, a geoelectrical survey using the electrical resistivity tomography methodology was used in three areas near the King Sejong Korean Antarctic Station. The geoelectrical models obtained for most of the profiles in the three areas of this work indicate that permafrost exists at depths deeper than 0.6 m. Because of lack of vegetation information no correlation between the electrical resistivity values and the existence of mosses and liquens at the surface of the ground can be inferred. More geoelectrical surveys are necessary. Some care should be taken, though, when doing the geoelectrical work because the ground near the King Sejong Antarctic Station presents very high electrical ground resistances.